Fan Pages On The Customer-Brand Relationship and Its Motivation To Participate: A Conceptual Paper - Raihatul Jannah, Ahmad; Puteri Fadzline, Muhamad Tamyez (Penerbit Universiti Malaysia Pahang, 2015)
The purpose of this conceptual paper is to review the relationship between customers and their motivations to participate in Facebook fan pages. It defines and presents the effects of fan pages in a manner that shed light on the constructs and sets the stage for future research. This article also explores its factors that contribute to the participation in fan pages of social network as well as a thorough understanding of why an attraction of fan pages among customers exists and whether customer integration and engagement effects on their brand loyalty. This will further determine whether companies do benefit from their brands’ Facebook fans. This paper provides a conceptual framework for considering predictors of participation in fan pages of social network. It indicates factors that contribute to the consequence as well as practical insights for managers.